2022
DOI: 10.1099/acmi.0.000322
|View full text |Cite
|
Sign up to set email alerts
|

Dominant remodelling of cattle rumen microbiome by Schedonorus arundinaceus (tall fescue) KY-31 carrying a fungal endophyte

Abstract: Tall fescue KY-31 is an important primary forage for beef cattle. It carries a fungal endophyte that produces ergovaline, the main cause of tall fescue toxicosis that leads to major revenue loss for livestock producers. The MaxQ, an engineered cultivar, hosts an ergovaline nonproducing strain of the fungus and consequently is nontoxic. However, it is less attractive economically. It is not known how rumen microbiome processes these two forages towards nutrient generation and ergovaline transformation. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…In most cases there is little information on the association of isolate genomes, MAGs, and even sometimes the metatranscriptomic and metaproteomic data for the methanogens with the following key parameters: (i) details of the feed; (ii) spatial location within the rumen, namely, fiber-associated, planktonic, and epimural microbiome; (iii) co-occurrence, such as association with the syntrophic partners, protozoa, and bacteria; (iv) timing of sampling with respect to feeding; and (v) comparison with free-living counterparts. In a recent study with cattle grazing tall fescue, a major perturbation of the microbiome by a toxic version of the grass was detected only when the sessile and planktonic fractions were analyzed separately (Khairunisa et al, 2022) and similar observations have been reported by others (Pitta et al, 2014).…”
Section: Harnessing Omics Approach For Analyzing Metabolism Of Rumen ...supporting
confidence: 75%
“…In most cases there is little information on the association of isolate genomes, MAGs, and even sometimes the metatranscriptomic and metaproteomic data for the methanogens with the following key parameters: (i) details of the feed; (ii) spatial location within the rumen, namely, fiber-associated, planktonic, and epimural microbiome; (iii) co-occurrence, such as association with the syntrophic partners, protozoa, and bacteria; (iv) timing of sampling with respect to feeding; and (v) comparison with free-living counterparts. In a recent study with cattle grazing tall fescue, a major perturbation of the microbiome by a toxic version of the grass was detected only when the sessile and planktonic fractions were analyzed separately (Khairunisa et al, 2022) and similar observations have been reported by others (Pitta et al, 2014).…”
Section: Harnessing Omics Approach For Analyzing Metabolism Of Rumen ...supporting
confidence: 75%
“…Various studies suggest that certain millipede gut bacteria possess enzymes for breaking down plant polysaccharides (2024). If millipedes rely on cellulose for their nutrition, extensive fermentation followed by methanogenesis, similar to ruminants or wood-feeding termites, should occur in their guts (7, 25). However, methanogenesis has only been observed in some millipede species, but not others, with its occurrence correlated to the millipede size (26).…”
Section: Introductionmentioning
confidence: 99%